Osteogenic potential of human adipose derived stem cell co-culture with human osteoblast on titanium dioxide nanofibrous surface - Ismail, Rozila; Tan, A. W.; Pingguan-Murphy, Belinda; Sha'ban, Munirah; Chua, Kien Hui (Tissue Engineering and Regenerative Medicine Society of Malaysia, 2014)
The study aims to evaluate the osteogenic potential of human adipose derived stem cell (HADSC) co-culture with human osteoblast (HOB) using selected HADSC/HOB ratio of 2:1, 1:1 and 1:2, respectively. The HADSC/HOB was seeded on Titanium dioxide (TiO2) coated with or without nanofibre substrate. The non-coated TiO2 was used as control. The effects of TiO2 based scaffolds on cell adhesion were characterized by scanning electron microscopy (SEM). Cell viability, differentiation and mineralization were assessed by Alamar Blue, alkaline phosphatase (ALP) and Alizarin Red assays, respectively. The combination of HADSC/HOB, 2:1 ratio, seeded on nanofibrous-coated TiO2 showed better cell adhesion, viability, differentiation and mineralization than the other groups. This study offers opportunity to assess in vitro cellular development of HADSC through direct cell to cell contact with HOB. This study indicates that the co-cultured HADSC/HOB seeded on TiO2 based scaffolds may serve as a promising approach to facilitate osteogenic differentiation activity.